Autoethnographic Methodology and its Applicability to Psychological Research and Practitioners - Ally, Yaseen (PINS-Psychology in Society, 2022)
Despite psychology’s primary focus – understanding of human behaviour, there is a long tradition that excludes the voices of psychological practitioners from the content they investigate. In fact, publications in psychology that draw on reflexive methodologies are scant and not readily available or sought after. In this paper, I argue that autoethnographic methodology can contribute meaningfully to knowledge production in psychology. It is argued, that by virtue of its paradigmatic and methodological characteristics, autoethnographic research could allow psychological practitioners to reflect and share their lived experiences in the production of knowledge. These personal experiences, are unfortunately, not adequately captured, documented and shared. The transformation of psychological methodology has become a key feature in the decolonial project, that resonates with the current South African trajectory set in motion by students, calling for more contextualised and relevant knowledge systems. In this paper, I present the key features of autoethnographic methodology and argue for its relevance in psychological knowledge production. I also argue that through the implementation of autoethnographic methodology, the psychological practitioner, by virtue of lived experiences, will be able to generate knowledge that can be utilized both in theory development and therapeutic settings.